Herói popular sob ironia na cena política: estudo sobre o personagem e o entrelaçamento entre ficção e realidade nos filmes Macunaíma (1969) e Terceiro Milênio (1982) - Araújo, Mauro Luciano Souza de (2010)
The dissertation leans over an analysis of aspects of the mise-en-scène at the two chosen films, having focus in the fictional and non-fictional character rendered ironical in the Cinema Novo s (brazilian new cinema) stage political scene, real scene and at the context during the intensification of a conservative modernization: 1 - Macunaíma (1969), of Joaquim Pedro de Andrade; 2 - Terceiro Milênio (1982), of Jorge Bodanzky and Wolf Gauer. Those are two manners of facing the character - of one side ficcional, with origins in the oral tradition of Amazonian legends, transformed in protagonist of a modernist book by Mário of Andrade, later converted in cinema´s character; on the other side the political protagonist's direct filmed in performance for the documentary -, these two lines have its crossing point that allows an observation of a national type, involved in the double-dealing, of Iberian root sighted in the cunning, a type of the subverted epic's hero. This modern character's in the visual expression fall down in the type of the flâneur, bohemian, roguish - the disinterested or inapt Brazilian hero.